Epispadias repair with tunica vaginalis flap. Issue 5 (October 2017) - Zee, R.S.; Makari, J.H.; Ferrer, Fernando; Herndon, C.D.A.
Summary: Introduction: Primary epispadias is a rare congenital malformation that afflicts about 1 in 80, 000 children. The surgical repair, originally described by Cantwell over 100 years ago, is fundamentally sound and incorporates several important steps to achieve an optimal result. Methods: A 9-month-old male with penopubic epispadias presented for surgical repair. Pre-operative imaging included a normal renal ultrasound and voiding cystourethrogram that demonstrated a moderate-sized bladder, partially competent bladder neck, and no vesicoureteral reflux. A modified Cantwell–Ransley approach to the repair was performed without complete disassembly of the penis. Established surgical principles of identification of laterally placed neurovascular bundles, preservation of the ventral mesentery to the urethral plate, mobilization of the urethral plate off the corporal bodies with ventral relocation, and dorsal medial rotation of the corporal bodies are demonstrated in this video. Results: This procedure was performed as an outpatient. The patient had an unremarkable postoperative course. The #6-French urethral stent was removed on postoperative day 10. Conclusions: This video demonstrates a modified Cantwell–Ransley technique for epispadias repair, which employs a tunica vaginalis flap to reinforce the urethral repair. The adherence to surgical principles described by Cantwell in the late 1800s for children with primary epispadias continues to lead optimal surgical outcomes.